PENGARUH PEMBELAJARAN TECHNOPRENEURSHIP TERHADAP INTENSI TECHNOPRENEURSHIP MELALUI KESADARAN INOVASI TEKNOLOGI DAN EFIKASI DIRI PADA SISWA SMK DI MOJOKERTO - Rani Julia Pratiwi; Wening Patmi Rahayu; Ludi Wishnu Wardana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of technopreneurship learning on technological innovation awareness and technopreneurship intention, with self-efficacy as a mediator, among vocational high school students in Mojokerto. An explanatory quantitative survey involved 238 grade XI and XII students in Digital Business and Retail Business programs at seven schools. Data was analyzed using SEM-PLS. Technopreneurship learning positively and significantly affected technological innovation awareness and technopreneurship intention. Technological innovation awareness and self-efficacy significantly affected intention and mediated the learning-intention relationship. The findings support strengthening technology-based experiential learning and students’ self-efficacy in vocational entrepreneurship education. Keywords: Technopreneurship Learning; Technological Innovation Awareness; Self-Efficacy; Technopreneurship Intention